Paleomagnetism of the Proterozoic Wathaman batholith and the suturing of the Trans-Hudson orogen in Saskatchewan - Symons, D. T. A. (Canadian Journal of Earth Sciences, 1991)
The Wathaman (Wathaman–Chipewyan) batholith is an 1854 ± 11 Ma, northeast-trending, homogenous, felsic pluton that is over 900 km long. It is thought to be a magmatic arc, with the Archean Hearne craton on its northwestern side as the hinterland and the remains of the Early Proterozoic Manikewan oceanic crust of the Trans-Hudson orogen on its southeastern side. Alternating-field and thermal step demagnetization methods isolate an A remanence component with a mean direction of D = 134.6°, I = 54.1° (α 95 = 3.5°, k = 94, N = 19). Isothermal remanent magnetization tests confirm that this A magnetization component is preserved in pseudosingle to multidomain magnetite and in hematite. Contact tests with intruded older rocks of the Peter Lake domain, with younger crosscutting mafic dikes and with younger crosscutting shear zones, indicate that A is a primary remanence. Its pole position of 67°W, 9°N (dp = 3°, dm = 5°) confirms that it was formed along the margin of the Slave–Rae–Hearne craton, supporting tectonic models that it records a suture zone. It also indicates that the LaRonge – Lynn Lake domain, Flin Flon domain, and Superior Province were translated relatively northwestward into the suture by at least 11 ± 11°, 27 ± 12°, and 49° ± 16°, respectively, as the Manikewan Ocean closed.